2021
DOI: 10.1097/jhm-d-20-00157
|View full text |Cite
|
Sign up to set email alerts
|

Reported Clinical and Financial Performance of Hospitals With Physician CEOs Compared to Those With Nonphysician CEOs

Abstract: EXECUTIVE SUMMARY Little work has been done comparing the performance of hospitals with physician CEOs versus nonphysician CEOs, despite the ease of identifying this characteristic and extant leadership theories suggesting a relationship between technical expertise and success in leading highly technical organizations. We performed a detailed analysis of several widely accepted measures of clinical and financial performance across a randomly selected group of U.S. acute care hospitals with more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Tasi and colleagues found that physician-led hospital systems had higher quality ratings compared with nonphysician-led hospital systems. Yet, a recent publication by Moores and colleagues found a significantly higher 30-day cardiovascular mortality rate in physician-led hospitals (80 deaths) when compared with nonphysician led hospitals (72 deaths), but the association was nullified in the multivariate linear regression analysis. The authors suggested that this trend may influence clinical outcomes, yet temporality could not be established because of the study design .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tasi and colleagues found that physician-led hospital systems had higher quality ratings compared with nonphysician-led hospital systems. Yet, a recent publication by Moores and colleagues found a significantly higher 30-day cardiovascular mortality rate in physician-led hospitals (80 deaths) when compared with nonphysician led hospitals (72 deaths), but the association was nullified in the multivariate linear regression analysis. The authors suggested that this trend may influence clinical outcomes, yet temporality could not be established because of the study design .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a recent publication by Moores and colleagues found a significantly higher 30-day cardiovascular mortality rate in physician-led hospitals (80 deaths) when compared with nonphysician led hospitals (72 deaths), but the association was nullified in the multivariate linear regression analysis. The authors suggested that this trend may influence clinical outcomes, yet temporality could not be established because of the study design . Additionally, the authors noted that future research should include CEOs with 3 years of tenure, which was unaccounted for in our cross-sectional design …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly however, only a few studies have compared the performance of hospitals with physician Chief Executive Officers (CEOs) to that of hospitals with non-physician CEOs (Moores et al, 2021;Sarto and Veronesi, 2016;Satiani and Prakash, 2016;Tasi et al, 2019). Studying the relationship between physician leadership and hospital performance could lead to a more focused approach to leadership training and development and improve hospital succession planning.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, scholars and practitioners have questioned whether the hospital's chief executive officer and board of directors should be clinically trained top executives (Kakemam and Goodall, 2019;Davlyatov et al, 2021;Moores et al, 2021). The empirical evidence suggests that clinicians' involvement in leadership positions varies significantly across countries.…”
Section: Introductionmentioning
confidence: 99%